Review on Pathogenic Bacteria Listeria monocytogenes, the Detection and the Sequencing Gene Methods Isolated from Meat Products - Bhakti Etza Setiani; Yoyok Budi Pramono; Lutfi Purwitasari (Journal of Applied Food Technology, 2019)
A study was conducted to review on pathogenic bacteria Listeria monocytogenes, the detection and the sequencing gene methods isolated from meat products, compare selected methods that detect the presence of L. monocytogenes in selected raw and processed meat products. L. monocytogenes (originally named Bacterium monocytogenes) is a gram-positive, non-sporeforming, highly mobile, rod-type, and facultative anaerobic bacterium species. It can grow under temperatures between -1.5 to 45°C and at pH range between 4.4 and 9.4, with the optimum pH of 7. Rapid methods (PCR based and VIDAS-LDUO®) detected L. monocytogenes faster than the conventional method. It was also gathered that Phenotypic identification and Genotypic identification were two types of confirmation test for L. monocytogenes. L. monocytogenes can be found in raw meat and meat product because of environmental contamination, cross contamination or error process.